유체 플라즈마 방식을 사용한 은 나노파티클의 합성 - 유승철(Seung-cheol Yoo); 신홍직(Hong-Jik Shin); 최원석(Won Seok Choi) (전기학회 논문지 P권, 65(3), 2016)
In this study, we used not chemical and physical synthesis method but the solution plasma sputtering method in the synthesis of silver nano-particles. Synthesis of all the silver nano-particles was conducted for 1hour in 360 ml of distilled water and characteristics of changing the input voltage and frequency of the synthesised silver nano-particles by using the solution plasma sputtering method were analyzed through FE-SEM(Field Emission-Scanning Electron Microscope). We changed the input voltage from 8 kV to 10 kV in steps of 1 kV, input frequency from 20 kHz to 30 kHz in steps of 5 kHz in the solution plasma reactor with the advanced device which can control the DC voltage and frequency. We confirmed that the size of silver nano-particles were larger according to the change of the input voltage and frequency.